Evaluacion de resistencia del frijol al Apion godmani en Judapa Guatemala - Beebe, Stephen E.; Salguero, V (International Center for Tropical Agriculture, 1982)
At the Apion nursery, Asuncion Mita, Jutiapa, several entries from the Guatemalteco Germplasm Bank (some formerly reported as resistant), entries from CIAT preliminary yield trials (EP-81), and individual selections from Linea 17 and from the International Apion Nursery were assessed for resistance to the bean pod weevil, Apion godmani. Cv. were planted in rows 3 m long with 3 replications. Plants were artificially infested during flowering by adults captured in the Golden Mosaic Nursery. After most of the cv. reached physiological maturity, 30 pods/row/var. were collected and evaluated to determine the percentage of damaged seed. Linea 17 from El Salvador was used as resistant check. At the 1981 International Nursery, Linea 17 had 3 percent damaged grain; and several of its descendent lines (bright red-seeded) were equally resistant. At this nursery, the most susceptible cv. had 36 percent damaged seed. Guate and EP-81 entries had geater pressure from Apion as indicated by the 11 percent damage in Linea 17 seed. The best Guate entry was Guate-989 with 6 percent damage. The best EP- 81 entry was a Brazilian var., CATU, with 8 percent damage. EP-81 entries also showed resistance to common bacterial blight (Xanthomonas phaseoli), Empoasca, rust (Uromyces phaseoli), web blight (Thanatephorus cueumeris), and anthracnose (Colletotrichum lindemuthianum). Tamazulapa, a BGMV-tolerant var. from ICTA, also presented a low percentage of damage. (AS-CIAT)